Biochemical and histopathological responses in peripubertal male rats exposed to agrochemicals isolated or in combination: A multivariate data analysis study. (15th January 2021) - Aranha, Maria Luiza Garcia; Garcia, Mariana Simões; de Carvalho Cavalcante, Deborah Navit; Silva, Ana Priscila Gomes; Fontes, Mayana Karoline; Gusso-Choueri, Paloma Kachel; Choueri, Rodrigo Brasil; Perobelli, Juliana Elaine
Graphical abstract: Highlights: Agrochemicals toxicity to juvenile rats was assessed alone or in combination. DNA damage and activation of the xenobiotic biotransformation system were observed. Isolated substances caused mobilization of cell defense and hepatotoxicity. Binary mixtures also induced GST activity and caused liver tissue alterations. Ternary mixture did not exacerbate effects probably due to chemical interactions. Abstract: The widespread use of agrochemicals results in the exposure of the general human population, including children, to several of these chemicals simultaneously. In the present preclinical study, it was investigated the hepatic damages caused by exposure to acephate, carbendazim and mancozeb when administered alone or in different combinations (binary and ternary). Juvenile male Wistar rats were exposed to agrochemicals from post-natal day 53, by gavage. The doses of agrochemicals applied here were determined from previous studies whose results showed no signs of systemic toxicity. All exposures provoked a significant increase in DNA damage (except for acephate alone) and activation of the xenobiotic biotransformation system (except for the ternary mixture). Interestingly, the ternary mixture did not exhibit an exacerbation in adverse effects caused by agrochemicals isolated or in binary combination, even though they are sharing genotoxicity damage induction as a common toxicity pathway. Conversely, some effects observed for isolated or binary combinations of agrochemicals were not observed for ternary combination, suggesting a chemical interaction that could imply antagonism character. Using a multivariate data analysis approach, exposure to isolated agrochemicals were related to a group of adverse effects characterized by hepatic lesion and the attempt of the tissue to mobilize defense cells and increase mitotic rates to minimize damages. Binary mixtures also share similarities in relation to the effects they exhibited, mainly a moderate to high increase in the GST activity and in histopathological alterations suggesting that binary combinations trigger an increased response of the mechanism of xenobiotics biotransformation. Together, obtained results bring important insights regarding adverse effects and possible interaction of the three agrochemicals whose residues are commonly detected in agro-food products.